Health benefits of bioactive molecules from spices and aromatic plants - S J Mariwala, M Gunasekar, K Geemon, (Journal of Spices and Aromatic Crops, 2012)
Spices are essentially used to improve the appeal and sensory characteristics of food. The bioactive compounds, which are the key natural flavour and fragrance ingredients of various spices and other aromatic plants play a vital role in healthcare. These are discussed with reference to the recent research carried out in anti-inflammatory, anti-arthritic, neuro-protective, cardiovascular, diabetic support, body weight management, wound healing, antioxidants, antimicrobial as food preservatives, ocular and oral health as well as in aroma-therapy with emphasis on human health and green chemistry.